Affect lability predicts occurrence of suicidal ideation in bipolar patients: a two‐year prospective study. (5th March 2017) - Ducasse, D.; Jaussent, I.; Guillaume, S.; Azorin, J. M.; Bellivier, F.; Belzeaux, R.; Bougerol, T.; Etain, B.; Gard, S.; Henry, C.; Kahn, J. P.; Leboyer, M.; et al.
Abstract : Objective: The aim of our study was to investigate, in bipolar patients, whether affect lability was associated with suicidal ideation incidence during 2‐year follow‐up, and which subtype of affect lability was associated with suicidal ideation. Method: A total of 319 euthymic or mildly depressed bipolar outpatients recruited in the French FondaMental Advanced Centres of Expertise for Bipolar Disorder were divided into two subgroups according to the occurrence of suicidal ideation during a 2‐year follow‐up. Affect lability was assessed by the French version of the Affect Lability Scale. Results: Bipolar patients with high affect lability were more likely to report suicidal ideation during follow‐up, even after adjustment for age, study level, rapid cycling, current depression level, anxiety disorder, and lifetime history SA (OR = 2.47; 95% CI [1.15–5.30], P = 0.01). The risk of suicidal ideation increased with the level of affect lability. More specifically, the propensity to switch from neutral to elation affect, from anxious to depressive affect (or inversely), and from neutral to anger affect predicted suicidal ideation. Conclusion: Reducing affective lability could become a new therapeutic target of suicidal prevention in bipolar disorder.